The Influence of Blockchain Technology and Digital Marketing in Improving Banking Services at Bank Permata Bali - Keniciro Yamamoto Tanoto (Jurnal Sistim Informasi dan Teknologi, 2025)
The Influence of Blockchain Technology and Digital Marketing in Improving Banking Services at Bank Permata Bali. This study aims to determine whether blockchain technology and digital marketing benefit from facilitating payments through digital banking, especially among Gen Z. This research method uses a quantitative research design. The data collection technique used was the Slovin Technique, and a sample of 50 respondents was used. The sampling technique used in this study uses non-probability sampling with the population size in this study taken from bank users, mainly Generation Z. The scale used is the Likert scale, the technique of data influence using Homogeneity, Heteroscedasticity, Autocorrelation, and Normality test. Classical assumptions use the validity test, Multiple linear regression, and Reliability.